A method for preparing activated carbon based on catalytic etching regulation of pore structure

CN122977381APending Publication Date: 2026-10-27CHINA UNIV OF PETROLEUM (EAST CHINA)
View PDF 4 Cites 0 Cited by

Patent Information

Application Number
CN202611140593.0
Authority / Receiving Office
CN · China
Patent Type
Applications(China)
Current Assignee / Owner
Filing Date
2026-07-30
Publication Date
2026-10-27

AI Technical Summary

Technical Problem

然而,所报道的化学活化主要使用固相混合,碱只附着在前驱体的表面,短时间通入CO2或水蒸气主要目的是为了快速造孔,其使用的碱量与常规方法没有差别,CO2或水蒸气只是为了追求更大的比表面积,与我们的发明在原理、目的和实施方面均有本质差别

Benefits of technology

[0043]1、工业制备活性炭时,使用的碱量十分大,对设备会造成比较严重的腐蚀作用,在后续的酸洗过程中也会消耗大量资源,本发明可以使碱量比常规方法减少3-5倍,并且能制备出高比表面积活性炭并且孔径可调的活性炭,在环境保护、能源存储、化工催化等领域有着良好的表现。

✦ Generated by Eureka AI based on patent content.

Smart Images

  • Figure CN122977381A_ABST
    Figure CN122977381A_ABST
Patent Text Reader

Abstract

The present application relates to a kind of active carbon preparation method based on catalytic etching regulation pore structure, alkali metal hydroxide catalytic activator is dissolved in deionized water, it is uniformly adsorbed and anchored in the inside or porosity of carbonaceous precursor by impregnation method, and the supported precursor is obtained after drying;Subsequently, heat preservation is carried out under inert atmosphere, and first activation is carried out, so that solid-solid reaction occurs between catalytic activator and precursor, and intermediate product with catalytic activity is generated;After first activation, atmosphere is switched to carbon dioxide or water vapor, catalytic etching is carried out at higher temperature, the catalytic effect of active substance remaining in first activation on gasification reaction is utilized, etching gas is reacted with carbon skeleton, so that the regulation of the degree of micropore to mesopore conversion is realized;Finally, after pickling, washing, drying, crushing and secondary heat treatment, active carbon product is obtained.The present application adopts step-by-step activation and etching process, realizes the uniform loading of catalytic activator by impregnation method, and utilizes the synergistic effect of two-step reaction to regulate pore structure, which is simple, and raw material is suitable, and provides an effective technical path for the preparation of high-purity active carbon.
Need to check novelty before this filing date? Find Prior Art

Description

Technical Field

[0001] This invention relates to the field of new materials and their preparation technology, specifically to a method for preparing activated carbon based on catalytic etching to regulate pore structure. Background Technology

[0002] Activated carbon, as a porous carbon material, plays an irreplaceable role in environmental protection, energy storage, and chemical catalysis due to its unique adsorption properties and catalytic carrier function. Its superior performance mainly stems from its well-developed pore structure and large specific surface area. Currently, the preparation methods of activated carbon are mainly divided into physical activation and chemical activation. Physical activation typically involves reacting carbonaceous precursors with gaseous activators such as water vapor, CO2, or air at high temperatures. Its advantage lies in its relatively simple process and lack of corrosive chemicals. However, physical activation has significant limitations, such as high activation temperature, high energy consumption, low specific surface area and yield, and difficulty in controlling the pore structure. Chemical activation involves mixing carbonaceous precursors with chemical activators and carbonizing and activating them at lower temperatures. Chemical activation can yield activated carbon with a larger specific surface area than physical activation. However, its drawbacks are also significant; the use of highly corrosive activators causes severe wear and tear on reaction equipment, significantly increasing equipment maintenance and replacement costs. Activated carbon obtained through activation with ZnCl2 and H3PO4 has a relatively low specific surface area, primarily limiting its application to low-value-added sectors. Furthermore, the chemical activation process requires large quantities of activating agents and generates significant amounts of wastewater containing corrosive chemicals during subsequent washing. This wastewater necessitates complex and expensive treatment processes to meet environmental emission standards, along with waste alkali recovery, resulting in a severe environmental burden and resource waste. The high cost of chemical activation also hinders its large-scale industrial application.

[0003] Physical and chemical activation are currently the mainstream methods for activating activated carbon, but their drawbacks are also significant. Improving activation efficiency, reducing costs, and minimizing environmental pollution are the main goals. Therefore, researchers have proposed some improvement methods. Among them, the most significant is the combined physical and chemical activation to prepare activated carbon. For example, patent CN113401900A uses a combined physical and chemical activation technology to prepare activated carbon. This patent uses an alkali metal salt with added catalyst as a chemical activator and introduces activation gases such as water vapor or CO2 during the activation stage to achieve physical and chemical coupling activation. Patent CN121687235A treats coal raw materials through physical activation and chemical modification, precisely controlling the ratio of micropores to mesopores to adapt to the diffusion requirements of different molecular sizes. This patent points out that physical and chemical activation methods can be used in combination to control the pore structure of activated carbon. Modifying carbon-rich precursors is also a mainstream approach. Modification makes them easier to activate and increases their affinity for chemical activators, thereby improving the utilization rate of the activators. For example, patent CN1843906A first oxidizes petroleum coke, then mixes the oxidation product with 1-5 parts of KOH for activation, yielding a product with a specific surface area of ​​2000 m². 2 While these methods reduce the amount of strong alkali used and the preparation cost to some extent, and increase the specific surface area of ​​activated carbon, they do not fundamentally change the core problems in the activated carbon production process. Activation still requires a high alkali-to-carbon ratio (above 1:1), which can still cause equipment corrosion and makes it difficult to meet the actual needs of efficient production.

[0004] In recent years, methods for preparing activated carbon through catalytic activation have attracted attention. These methods enhance the physical activation effect of steam or CO2 by adding transition metal compounds as catalysts. For example, patent CN102602928A uses metal oxides as catalysts, and patent CN104916452A uses Ni(NO3)2 solution to impregnate the precursor, preparing activated carbon through steam activation. While these methods use reagents with low corrosivity, they typically have several problems. First, the catalyst dosage is large. Due to the poor surface affinity between polar metal compounds and non-polar carbon precursors, the catalyst is difficult to disperse uniformly, requiring a large amount to achieve the desired activation effect. Furthermore, post-processing is complex and costly, requiring extensive acid washing after activation to remove residual metal catalyst, increasing the complexity and cost of post-processing and potentially introducing new environmental problems. Patent CN111689494A describes a non-corrosive catalyst and a method for preparing activated carbon through catalytic activation. This patent uses potassium salts, transition metal salts, and surfactants to create an affinity catalyst, obtaining activated carbon with a large specific surface area at ultra-low dosages and in ultra-short activation times. However, this method requires the preparation of a catalyst in advance, which is then mixed with a carbon precursor. This process increases costs, and the presence of transition metal salts adds a subsequent impurity removal and demagnetization process, which is not conducive to the low-cost preparation of activated carbon.

[0005] Therefore, given the rapid iteration and upgrading of energy storage and environmental protection materials and technologies, developing a new method that can effectively reduce the amount of activator used, reduce equipment corrosion, reduce environmental pollution, and efficiently prepare activated carbon with a large specific surface area is a key issue that urgently needs to be addressed in the field of activated carbon preparation.

[0006] It is particularly important to emphasize that there is a significant difference between granular activated carbon used for adsorption and powdered activated carbon used for energy storage. Compared to granular activated carbon used for adsorption, activated carbon for energy storage not only requires a larger specific surface area but also an adjustable pore structure to adapt to the energy storage needs of different scenarios. However, current conventional chemical activation methods, physical activation methods, and combined physicochemical activation methods all struggle to control the pore structure of activated carbon. Template methods can meet the requirements to some extent, but their high cost does not meet the needs of practical production. Therefore, developing a pore-adjustable activated carbon preparation route is of paramount importance in the current field of activated carbon research.

[0007] This invention differs from conventional physical activation, chemical activation, and the recently popular catalytic activation. Physical activation (CO2 or steam) is simple but time-consuming, energy-intensive, and yield-low; chemical activation (KOH, etc.) is highly efficient but the reagents are highly corrosive and cause heavy pollution; in recent years, catalytic activation has introduced metal catalysts such as Fe and Ni, which can promote pore formation but result in residual magnetic metals on the activated carbon, making it unsuitable for direct electrochemical use and requiring additional demagnetization and impurity removal, greatly increasing costs.

[0008] The core technical advantages of this invention are as follows: First, it employs a stepwise process of activation in an inert atmosphere followed by switching the etching gas, resulting in high reaction efficiency, short process time, low energy consumption, and higher overall efficiency. Second, the precursor and catalytic activator are mixed in a solution system, and then the solvent is removed by evaporation, allowing the catalytic activator to be directly adsorbed and firmly anchored within the precursor. This mixing method offers advantages such as simple operation, high efficiency, and outstanding mixing effect. Third, the catalytic activator uses alkali metal hydroxides such as NaOH, KOH, and CsOH, which do not introduce any magnetic metals. Subsequent acid washing and water washing can completely remove them, leaving no magnetic residue in the product. This eliminates the need for a demagnetization process, allowing it to be directly used for electrochemical energy storage. Fourth, it has extremely wide raw material adaptability, capable of processing polymer precursors, micron-sized carbon materials, and millimeter-sized carbon materials, with etching parameters optimized for different scales. Fifth, the pore size is precisely controllable, resulting in activated carbon with a very high specific surface area.

[0009] The innovative mechanism of this invention is as follows: A catalytic activator is anchored in the precursor. First, a pore-forming process is achieved through a chemical reaction between the catalytic activator and the carbon-rich precursor at high temperature. Then, CO2 or water vapor is used to catalytically etch and expand the pores in the pre-pored carbon-rich precursor. Under an inert atmosphere of 600-900 °C, the reaction between the alkali and carbon is a simple solid-solid reaction. During the catalytic etching process, when the reaction is switched to CO2 or water vapor, CO2 or water vapor also reacts with the carbon. This stage combines solid-solid and gas-solid reactions. The reaction during the initial activation in the entire activated carbon preparation process is as follows (taking KOH, the most commonly used KOH in industrial production, as an example):

[0010] 2KOH + C → K₂O + CO + H₂

[0011] 4KOH + C → K₂CO₃ + K₂O + H₂

[0012] K₂CO₃ + C → K₂O + 2CO

[0013] K₂O + C → 2K + CO

[0014] This process initially generates micropores and forms active substances such as carbonates, K₂O, and K. Subsequently, the process switches to CO₂ or water vapor at a higher temperature for catalytic etching, where the etching gas reacts with the carbon skeleton through a vaporization reaction.

[0015] C + CO₂ → 2CO

[0016] C + H₂O → CO + H₂

[0017] Experimental results show that the residual active substances such as carbonates, K₂O, and K after primary activation have a catalytic effect on the gasification reaction. Furthermore, by adjusting the etching temperature, time, and gas flow rate, the degree of transformation from micropores to mesopores can be precisely controlled, thereby achieving systematic regulation of pore size distribution. This two-stage independent optimization avoids the excessive corrosion of traditional chemical activation and overcomes the low efficiency of physical activation, while completely avoiding the problem of residual metal catalysts. This provides a new pathway for the green preparation of high-performance, high-purity activated carbon.

[0018] In summary, the principles, methods, objectives, and technical routes of this invention are significantly different from other patents. The combination of the precursor and alkali, primary activation, catalytic etching, and post-treatment have a strong correlation with product performance, and their combination has been verified through extensive experimental data. Compared to conventional physical activation, this invention significantly improves activation efficiency. Compared to conventional chemical activation, this invention effectively solves the equipment corrosion problems caused by the large amount of alkali used in existing technologies and the environmental pollution caused by subsequent acid washing, reducing the alkali content used during activation while increasing alkali utilization. While reducing costs, this method can produce activated carbon with the expected target pore structure. Therefore, the technical method proposed in this invention has significant innovation.

[0019] Furthermore, some patents and academic papers have reported methods to prepare activated carbon with a higher surface area by first chemically activating the precursor with alkali and then introducing CO2 or steam at the end of the activation process. However, the reported chemical activation mainly uses solid-phase mixing, with the alkali only adhering to the surface of the precursor. The short-term introduction of CO2 or steam is mainly for rapid pore formation, and the amount of alkali used is no different from conventional methods. The CO2 or steam is only used to pursue a larger specific surface area, which is fundamentally different from our invention in terms of principle, purpose, and implementation.

[0020] The key steps of this invention are the introduction of the catalytic activator and the catalytic activation step in the activation process. If the activator is not introduced or the catalytic activation step is not performed, the specific surface area of ​​the obtained activated carbon will be much smaller than that of the activated carbon modified by catalytic activation. Summary of the Invention

[0021] This invention proposes a method for preparing activated carbon based on catalytic etching to control pore structure. The method involves uniformly adsorbing and anchoring a catalytic activator within the interior or pores of a precursor, followed by a primary activation under an inert atmosphere, and then a catalytic etching step under CO2 or water vapor. After post-treatment, activated carbon with a high specific surface area and adjustable pore size is obtained. This invention is achieved through the following technical solution:

[0022] (1) First, dissolve the catalytic activator in a certain amount of deionized water to form a catalytic activator solution;

[0023] (2) The catalyst activator is uniformly adsorbed or anchored in the interior or pores of precursor A by impregnation, and then dried to prepare precursor B;

[0024] (3) First, the precursor B is heated to a set temperature under an inert atmosphere and kept at that temperature for a certain time to perform a first activation to obtain intermediate product C;

[0025] (4) Then switch the inert atmosphere to CO2 or water vapor, and continue to keep it at a certain temperature for a certain time to carry out catalytic etching to obtain intermediate product D;

[0026] (5) Wash, dry and pulverize intermediate product D;

[0027] (6) The washed and dried materials are subjected to secondary heat treatment.

[0028] Furthermore, the catalytic activator used in step (1) is one or more mixed catalytic activators selected from NaOH, KOH, and CsOH.

[0029] Furthermore, in step (1), the impregnation method requires the catalyst activator to be dissolved in deionized water to form a solution. 1 g of catalyst activator needs to be dissolved in 5-20 mL of deionized water.

[0030] Furthermore, the impregnation method in step (1) requires stirring at 45-60 °C to form a uniform dispersion of precursor A in the solution of catalytic activator.

[0031] Furthermore, the precursor A used in step (2) can be divided into three types: polymer precursor, micron-sized carbonized material, and millimeter-sized carbonized material. Among them, polymer precursor is an uncarbonized organic polymer, including but not limited to synthetic polymers such as phenolic resin, chitosan, lignin, and cellulose, as well as natural polymers; micron-sized carbonized material is a carbon-rich precursor obtained through pre-carbonization treatment, such as pre-carbonized biomass raw materials (coconut shell carbonized material, walnut shell carbonized material, apricot kernel carbonized material, etc.), and petroleum coke obtained by delayed coking, with a particle size range of 20-50 μm; millimeter-sized carbonized material is a carbon-rich precursor obtained through pre-carbonization treatment, such as pre-carbonized biomass raw materials (coconut shell carbonized material, walnut shell carbonized material, apricot kernel carbonized material, etc.), and petroleum coke and bituminous coal obtained by delayed coking, with a significant difference from micron-sized carbonized material in that its particle size range is 2-10 mm.

[0032] Furthermore, in step (2), the mass ratio of polymer precursor to catalytic activator is 1:0.05-1:1; the mass ratio of micron-sized carbonized material to catalytic activator is 1:0.2-1:2; and the mass ratio of millimeter-sized carbonized material to catalytic activator is 1:0.2-1:3.

[0033] Furthermore, in step (3), the initial activation is carried out at a heating rate of 0.5-10 °C / min, at a reaction temperature of 600-900 °C, and for a holding time of 0.5-5 h.

[0034] Furthermore, the intermediate product C obtained from the polymer precursor in step (4) undergoes a catalytic etching step where, after initial activation, the inert gas is switched to CO2 or water vapor for catalytic etching; wherein the CO2 catalytic etching temperature is 700-1000 °C, and the CO2 gas flow rate is 10-50 mL / min / g. 原料 Catalytic etching time: 0.5-3 h; water vapor catalytic etching temperature: 700-900 °C; water vapor flow rate: 5-20 mL / min / g 原料 The catalytic etching time is 0.1-1 h.

[0035] Furthermore, the intermediate product C obtained from the micron-sized carbonized precursor in step (4) undergoes a catalytic etching step as follows: after the initial activation, the inert gas is switched to CO2 or water vapor for catalytic etching. The CO2 catalytic etching temperature is 700-900 °C, and the CO2 gas flow rate is 20-80 mL / min / g. 原料 The catalytic etching time was 0.5-2 h; the water vapor catalytic etching temperature was 800-900 °C, and the water vapor gas flow rate was 5-30 mL / min / g. 原料 The catalytic etching time is 0.5-1.5 h.

[0036] Furthermore, the intermediate product C obtained from the millimeter-scale carbonized precursor in step (4) undergoes a catalytic etching step as follows: after the initial activation is completed, the inert gas is switched to CO2 or water vapor for catalytic etching. The CO2 catalytic etching temperature is 900-1000 °C, and the CO2 gas flow rate is 20-100 mL / min / g. 原料 The catalytic etching time was 1.5-2 h; the water vapor catalytic etching temperature was 900-950 °C, and the water vapor gas flow rate was 10-50 mL / min / g. 原料 The catalytic etching time is 1-2.5 h.

[0037] Furthermore, the washing in step (5) uses hydrochloric acid with a concentration of 0.1-2 mol / L, or a mixed acid consisting of 0.1-2 mol / L hydrochloric acid and 0.1-0.5 mol / L hydrofluoric acid.

[0038] Further, in step (5), the acid solution used is added to the intermediate product D at a mass ratio of 1:10 to 1:20 to obtain a mixed solution. Then, the solution is stirred and washed at a stirring speed of 100-250 r / min, a washing temperature of 50-90 °C, and a washing time of 12-36 h.

[0039] Further, in step (5), the pickled material is repeatedly washed with deionized water or distilled water until the pH value of the washing solution reaches neutral; the obtained material is then thoroughly dried at 110-150 °C.

[0040] Furthermore, in step (5), the fully dried material is crushed and sieved using an air classifier-equipped air classifier.

[0041] Furthermore, the secondary heat treatment in step (6) involves heating to 400-900 °C at a rate of 2-5 °C / min for inertization, with a holding time of 1-2 h, and the protective atmosphere is nitrogen or argon.

[0042] The present invention has the following advantages:

[0043] 1. In the industrial preparation of activated carbon, a large amount of alkali is used, which can cause serious corrosion to the equipment. It also consumes a lot of resources in the subsequent acid washing process. This invention can reduce the amount of alkali by 3-5 times compared with conventional methods, and can produce activated carbon with high specific surface area and adjustable pore size. It has good performance in environmental protection, energy storage, chemical catalysis and other fields.

[0044] 2. From a production perspective, this method uses universally applicable raw materials, has a simple preparation process, low cost, and low corrosion effect, providing a feasible approach for the preparation of high-performance activated carbon.

[0045] 3. From a practical application perspective, the specific surface area of ​​activated carbon prepared by catalytic etching strategy is much larger than that of activated carbon prepared by physical activation method, making it suitable for large-scale production. Attached Figure Description

[0046] Figure 1 This is a SEM image of the activated carbon prepared in Example 1 of the present invention;

[0047] Figure 2 This is a SEM image of the activated carbon prepared in Example 2 of the present invention;

[0048] Figure 3 This is a SEM image of the activated carbon prepared in Example 3 of the present invention;

[0049] Figure 4 This is a charge-discharge curve of the activated carbon-assembled double-layer capacitor prepared in Example 2 of the present invention;

[0050] Figure 5 This is a charge-discharge curve of the double-layer capacitor assembled with activated carbon prepared in Example 5 of the present invention.

[0051] Figure 6 This is a pore size distribution diagram of the activated carbon material prepared in Example 2 of the present invention;

[0052] Figure 7 This is the N2 isothermal adsorption-desorption curve of the activated carbon material prepared in Example 4 of this invention; Detailed Implementation Plan

[0053] The present invention will be described in detail below with reference to embodiments:

[0054] Example 1:

[0055] High specific surface area activated carbon was prepared according to the following method: 0.1 g KOH was weighed into a beaker, 2.0 mL deionized water was added, and the mixture was stirred at 50 °C to form a catalytic activator solution. Then, 1.0 g phenolic resin was weighed and added to the catalytic activator solution, and stirred for 4 h. The mixture was then thoroughly dried at 100 °C, and after drying, it was thoroughly ground and pulverized. The pulverized precursor was then activated once. The activation procedure was: under nitrogen protection, the temperature was increased to 700 °C at 1 °C / min and held for 1 h. Then, catalytic etching was performed. The catalytic etching procedure was: the nitrogen was switched to CO2, the temperature was increased to 800 °C at 10 °C / min and held for 1.5 h. After natural cooling, the activated product was treated with 2.0 mol / L hydrochloric acid to remove the catalytic activator, then washed with deionized water until neutral and dried. After pulverization and sieving, a second heat treatment was performed for inertization. The inertization procedure was: the temperature was increased to 800 °C at 5 °C / min. At °C, with a holding time of 1 h, a specific surface area of ​​1506 m² can be obtained. 2 / g activated carbon.

[0056] Example 2:

[0057] High specific surface area activated carbon was prepared according to the following method: 0.5 g KOH was weighed into a beaker, 10.0 mL deionized water was added, and the mixture was stirred at 40 °C to form a catalytic activator solution. Then, 1.0 g of micron-sized coconut shell carbonized material was weighed and added to the catalytic activator solution, and stirred for 3 h. The mixture was then thoroughly dried at 100 °C, and after drying, it was thoroughly ground and pulverized. The pulverized precursor was then activated once. The activation procedure was as follows: under argon protection, the temperature was increased to 800 °C at 5 °C / min and held for 1 h. Then, catalytic etching was performed. The catalytic etching procedure was as follows: the argon gas was switched to CO2, the temperature was increased to 850 °C at 5 °C / min and held for 0.4 h. After natural cooling, the activated product was treated with 1 mol / L hydrochloric acid to remove the catalytic activator, then washed with deionized water until neutral and dried. After pulverization and sieving, a second heat treatment was performed for inertization. The inertization procedure was as follows: the temperature was increased to 850 °C at 5 °C / min. At °C, with a holding time of 2 h, a specific surface area of ​​2342 m² can be obtained. 2 / g activated carbon.

[0058] Example 3:

[0059] High specific surface area activated carbon was prepared according to the following method: 0.5 g KOH was weighed into a beaker, 10.0 mL deionized water was added, and the mixture was stirred at 40 °C to form a catalytic activator solution. Then, 1.0 g of millimeter-sized coconut shell carbonized material was weighed and added to the catalytic activator solution, and stirred for 12 h. The mixture was then thoroughly dried at 110 °C, and after drying, it was thoroughly ground and pulverized. The pulverized precursor was then activated once. The activation procedure was as follows: under argon protection, the temperature was increased to 800 °C at 5 °C / min and held for 1 h. Then, catalytic etching was performed. The catalytic etching procedure was as follows: the argon gas was switched to CO2, the temperature was increased to 850 °C at 5 °C / min and held for 0.4 h. After natural cooling, the activated product was treated with 1.0 mol / L hydrochloric acid to remove the catalytic activator, then washed with deionized water until neutral and dried. After pulverization and sieving, a second heat treatment was performed for inertization. The inertization procedure was as follows: the temperature was increased to 850 °C at 5 °C / min. At °C, with a holding time of 2 h, a specific surface area of ​​2054 m² can be obtained. 2 / g activated carbon.

[0060] Example 4:

[0061] High specific surface area activated carbon was prepared according to the following method: 1.0 g of CsOH was weighed into a beaker, 20.0 mL of deionized water was added, and the mixture was stirred at 50 °C to form a catalytic activator solution. Then, 1.0 g of petroleum coke was weighed and added to the catalytic activator solution, and the mixture was stirred for 4 h. The mixture was then thoroughly dried at 100 °C, and after drying, it was thoroughly ground and pulverized. The pulverized precursor was then activated once. The activation procedure was as follows: under argon protection, the temperature was increased to 900 °C at 2 °C / min and held for 1 h. Then, catalytic etching was performed. The catalytic etching procedure was as follows: nitrogen was switched to CO2, the temperature was increased to 950 °C at 10 °C / min and held for 0.5 h. After natural cooling, the activated product was treated with 2.0 mol / L hydrochloric acid to remove the catalytic activator, then washed with deionized water until neutral and dried. After pulverization and sieving, a second heat treatment was performed for inertization. The inertization procedure was as follows: the temperature was increased to 750 °C at 2 °C / min. At °C, with a holding time of 3 hours, a specific surface area of ​​1626 m² can be obtained. 2 / g activated carbon.

[0062] Example 5:

[0063] High specific surface area activated carbon was prepared according to the following method: 1.0 g of micron-sized coconut shell carbonized material was weighed and directly activated once. The activation procedure was as follows: under argon protection, the temperature was increased to 800 °C at 5 °C / min and held for 1 h. Then, catalytic etching was performed. The catalytic etching procedure was as follows: nitrogen was switched to CO2, the temperature was increased to 850 °C at 5 °C / min and held for 0.4 h. After natural cooling, the activated product was acid-washed with 1.0 mol / L hydrochloric acid, then washed with deionized water until neutral and dried. After pulverization and sieving, a second heat treatment was performed for inertization. The inertization procedure was as follows: the temperature was increased to 850 °C at 5 °C / min and held for 2 h. The resulting activated carbon had a specific surface area of ​​1389 m². 2 / g activated carbon.

[0064] Example 6:

[0065] High specific surface area activated carbon was prepared as follows: 0.5 g KOH and 1.0 g micron-sized coconut shell carbonized material were weighed, thoroughly ground, and transferred to a ceramic boat. The pulverized precursor was then activated once. The activation procedure was as follows: under argon protection, the temperature was increased to 800 °C at 5 °C / min and held for 1 h. Catalytic etching was then performed. The catalytic etching procedure was as follows: nitrogen was replaced with CO2, the temperature was increased to 850 °C at 5 °C / min and held for 0.4 h. After natural cooling, the activated product was treated with 1.0 mol / L hydrochloric acid to remove the catalytic activator, then washed with deionized water until neutral and dried. After pulverization and sieving, a second heat treatment was performed for inertization. The inertization procedure was as follows: the temperature was increased to 850 °C at 5 °C / min and held for 2 h. This yielded a specific surface area of ​​1265 m². 2 / g activated carbon.

[0066] Example 7:

[0067] High specific surface area activated carbon was prepared as follows: 1.0 g of micron-sized coconut shell carbonized material was weighed into a ceramic boat and activated. The first activation procedure was as follows: under argon protection, the temperature was increased to 800 °C at a rate of 5 °C / min and held for 1 h without catalytic etching. After natural cooling, the activated product was acid-washed with 1.0 mol / L hydrochloric acid, then washed with deionized water until neutral and dried. After pulverization and sieving, a second heat treatment was performed for inertization. The inertization procedure was as follows: the temperature was increased to 850 °C at a rate of 5 °C / min and held for 2 h, resulting in a specific surface area of ​​745 m². 2 / g activated carbon.

[0068] Table 1 Implementation Plan Data

[0069] Activated carbon 1 Activated carbon 2 Activated carbon 3 Activated carbon 4 Activated carbon 5 Activated carbon 6 Activated carbon 7 Precursor types Phenolic resin Micron-sized coconut shell carbonized material Millimeter-sized coconut shell carbonized material petroleum coke Micron-sized coconut shell carbonized material Micron-sized coconut shell carbonized material Micron-sized coconut shell carbonized material Catalyst activator / mixing method KOH / Immersion Method KOH / Immersion Method KOH / Immersion Method CsOH / Immersion Method - KOH / Grinding method - The ratio of catalyst activator to precursor 0.1 0.5 0.5 1 - 0.5 - One-step activation process (heating rate / holding temperature / holding time) 1 °C / min / 700 °C / 1 h 5 °C / min / 800 °C / 1 h 5 °C / min / 800 °C / 1 h 2 °C / min / 900 °C / 1 h 5 °C / min / 800 °C / 1 h 5 °C / min / 800 °C / 1 h 5 °C / min / 800°C / 1 h Catalytic etching procedure (heating rate / temperature / holding time) 10 °C / min / 800 °C / 1.5h 5 °C / min / 850 °C / 0.4h 5 °C / min / 850°C / 0.4h 10 °C / min / 950 °C / 0.5 h 5 °C / min / 850 °C / 0.4h 5 °C / min / 850 °C / 0.4h - Inertization process (heating rate / temperature / holding time) 5 °C / min / 800 °C / 1 h 5 °C / min / 850 °C / 2 h 5 °C / min / 850 °C / 2 h 2 °C / min / 750 °C / 3 h 5 °C / min / 850 °C / 2 h 5 °C / min / 850 °C / 2 h 5 °C / min / 850°C / 2h <![CDATA[Specific surface area (m 2 / g)]]> 1506 2342 2054 1626 1389 1265 745 Average pore size (nm) 1.0 1.6 1.8 1.3 0.9 1.4 0.7 Capacitance of electric double-layer capacitor (F / g) 135 168 154 140 86 107 80

[0070] The above embodiments are merely preferred embodiments of the present invention and are not intended to limit the scope of protection. Based on the basic principles of the present invention, those skilled in the art can make various equivalent modifications or substitutions, and all such modifications should fall within the scope of the claims of the present invention.

Claims

1. A method for preparing activated carbon based on catalytic etching to regulate pore structure, characterized in that, The activated carbon preparation method specifically includes the following steps: a) First, the catalytic activator is uniformly adsorbed and anchored in the interior or pores of the precursor A to prepare the precursor B; b) The precursor B is heated to a set temperature and kept at that temperature for a certain time under an inert atmosphere to perform a first activation to obtain intermediate product C; c) The inert atmosphere is then switched to CO2 or water vapor, and the temperature is kept at a certain temperature for a certain time to perform catalytic etching to obtain intermediate product D; d) The intermediate product D is post-treated to obtain activated carbon.

2. The method for preparing activated carbon based on catalytic etching to regulate pore structure as described in claim 1, characterized in that, The catalytic activator is one or more mixed catalytic activators selected from NaOH, KOH, and CsOH; the precursor A can be divided into three types: polymer precursor, micron-sized carbonized material, and millimeter-sized carbonized material; wherein, the polymer precursor is an organic polymer that has not undergone pre-carbonization treatment, including but not limited to synthetic polymers such as phenolic resin, chitosan, lignin, and cellulose, as well as natural polymers; the micron-sized carbonized material is a carbon-rich precursor obtained through pre-carbonization treatment, such as pre-carbonized biomass raw materials (coconut shell carbonized material, walnut shell carbonized material, apricot kernel carbonized material, etc.), and petroleum coke obtained by delayed coking, with a particle size range of 20-50 μm; the millimeter-sized carbonized material is a carbon-rich precursor obtained through pre-carbonization treatment, such as pre-carbonized biomass raw materials (coconut shell carbonized material, walnut shell carbonized material, apricot kernel carbonized material, etc.), petroleum coke obtained by delayed coking, and bituminous coal, etc., and its significant difference from the micron-sized carbonized material is that its particle size range is 2-10 mm.

3. The method for preparing activated carbon based on catalytic etching to regulate pore structure as described in claim 1, characterized in that, The method of adsorbing and anchoring the catalytic activator onto precursor A is the impregnation method. The specific operation steps are as follows: add the catalytic activator to deionized water, 1 g of catalytic activator needs to be dissolved in 5-20 mL of deionized water to form a catalytic activator solution; then add precursor A and stir at 45-60 °C to form a uniform dispersion of precursor A in the catalytic activator solution. The dispersion was then dried at 100-150 °C to obtain precursor B.

4. The method for preparing activated carbon based on catalytic etching to regulate pore structure as described in claim 1, characterized in that, The mass ratio of precursor A to catalytic activator is as follows: the mass ratio of polymer precursor to catalytic activator is 1:0.05-1:1; the mass ratio of micron-sized carbonized material to catalytic activator is 1:0.2-1:2; and the mass ratio of millimeter-sized carbonized material to catalytic activator is 1:0.2-1:

3.

5. The method for preparing activated carbon based on catalytic etching to regulate pore structure as described in claim 1, characterized in that, The first activation step involves heating to a certain temperature at a certain rate under an inert atmosphere and holding at that temperature for a certain time. The inert atmosphere is high-purity nitrogen or argon, the heating rate is 0.5-10 °C / min, the reaction temperature is 600-900 °C, and the activation holding time is 0.5-5 h.

6. The method for preparing activated carbon based on catalytic etching to regulate pore structure as described in claim 1, characterized in that, The intermediate product C obtained from the polymer precursor undergoes a catalytic etching step where, after initial activation, the inert gas is directly switched to CO2 or water vapor for catalytic etching; wherein the CO2 catalytic etching temperature is 700-1000 °C, and the CO2 gas flow rate is 10-50 mL / min / g. 原料 The catalytic etching time is 0.5-3 h; the water vapor catalytic etching temperature is 700-900 °C, and the water vapor gas flow rate is 5-20 mL / min / g. 原料 The catalytic etching time is 0.1-1 h.

7. The method for preparing activated carbon based on catalytic etching to regulate pore structure as described in claim 1, characterized in that, The intermediate product C obtained from the micron-sized carbonized precursor undergoes a catalytic etching step as follows: after initial activation, the inert gas is switched to CO2 or water vapor for catalytic etching. The CO2 catalytic etching temperature is 700-900 °C, and the CO2 gas flow rate is 20-80 mL / min / g. 原料 The catalytic etching time was 0.5-2 h; the water vapor catalytic etching temperature was 800-900 °C, and the water vapor gas flow rate was 5-30 mL / min / g. 原料 The catalytic etching time is 0.5-1.5 h.

8. The method for preparing activated carbon based on catalytic etching to regulate pore structure as described in claim 1, characterized in that, The intermediate product C obtained from the millimeter-scale carbonized precursor undergoes a catalytic etching step as follows: after initial activation, the inert gas is switched to CO2 or water vapor for catalytic etching. The CO2 catalytic etching temperature is 750-1000 °C, and the CO2 gas flow rate is 20-100 mL / min / g. 原料 The catalytic etching time was 1.5-2 h; the water vapor catalytic etching temperature was 900-950 °C, and the water vapor gas flow rate was 10-50 mL / min / g. 原料 The catalytic etching time is 1-2.5 h.

9. The method for preparing activated carbon based on catalytic etching to regulate pore structure as described in claim 1, characterized in that, The post-processing steps include five steps: acid washing, water washing, drying, air jet milling and sieving, and inertization. Acid washing uses 0.1-2 mol / L hydrochloric acid, or a mixed acid consisting of 0.1-2 mol / L hydrochloric acid and 0.1-0.5 mol / L hydrofluoric acid, added at a mass ratio of 1:10-1:20 to obtain a mixed solution. The solution is then stirred and washed at 50-90 °C for 12-36 h. The acid-washed material is repeatedly washed with deionized or distilled water until the pH of the washing solution reaches neutral. The resulting material is then thoroughly dried at 110-150 °C. The dried material is then pulverized and sieved using an air jet mill equipped with a cyclone classifier. Subsequently, the pulverized and sieved material is inertized under a protective atmosphere by heating to 400-900 °C at a rate of 2-5 °C / min for 1-2 hours. h, the protective atmosphere is high-purity nitrogen or argon.

10. The activated carbon material prepared by the preparation method according to any one of claims 1-9, characterized in that, The specific surface area of ​​the activated carbon material is 1200-2500 m². 2 / g, particle size D 50 The pore size ranges from 5 to 15 μm; the pore size distribution is mainly concentrated in the range of 0.6 to 4.0 nm, and the average pore size is adjustable in the range of 0.8 to 1.8 nm.

Citation Information

Patent Citations

  • Method for preparing activated carbon and coproducing hydrogen by coal catalysis and activation

    CN102602928A

  • Wooden active carbon composite material for super capacitor and preparing method of wooden activated carbon composite material

    CN104916452A

  • Non-corrosive catalyst and method for preparing activated carbon through catalytic activation

    CN111689494A

  • Coordinated regulation and control method for pores and functional groups of coal-based activated carbon carrier

    CN121687235A